KAJIAN KETERSEDIAAN DAN PEMANFAATAN KREDIT UNTUK PETANI DI KELURAHAN MUARA FAJAR KECAMATAN RUMBAI KOTA PEKANBARU - Rini Nizar '; Latifa Siswati '; Mufti ' ' (PEKBIS, 2015)
This study aims to 1) assess existing credit and can be used by farmers, 2) examinethe characteristics of existing credit to agriculture and 3) find out the problems facedby farmers in obtaining credit in the village of Muara Fajar. Results indicate 1) thatthere is enough credit varies both formal financial institutions such as UEK_SP andBRI and non formal and Farmers Cooperative Oil Agent, 2) loans offered by financialinstitutions accessible to assist farmers in farming capital and 3) farmers generallydo not have significant problems in utilizing existing credit as long as the appropriateprocedure proposed by financial institutions that exist in the village of Muara FajarKeyword : Credit, characteristics, financial Institutions.